Legalitas Pesantren Sebagai Lembaga Pendidikan Keagamaan Masyarakat Indonesia - Syarifah Gustiawati Mukri; Gilang Rizki Aji Putra (UIN Syarif Hidayatullah Jakarta, 2022)
The Pesantren Law is an affirmation of the importance of Islamic boarding school which is currently known as the propagator of the Islamic concept of Washatiyah. The enactment of the Law on Islamic Boarding Schools will further expand and strengthen the solemnity of participants in various fields, especially in the aspect of tafaqquh fiddin, da'wah, community empowerment, and economic empowerment of the people, and many aspects others who often become the work of Islamic boarding schools. This article explores the process formulation of the Law on Islamic Boarding Schools, debates in articles and verses in the Law on Islamic Boarding Schools, and the role of Islamic social organizations, and political parties in the process formulation of the Law on Islamic Boarding Schools.